The Antecedent of Entrepreneurial Orientation: An Entrepreneurial Commitment View - Kusumawijaya, Ida Ketut (International Review of Management and Marketing, 2019)
This study purpose to predict entrepreneurial commitment as an antecedent of entrepreneurial orientation of SME employees in Bali. This research was conducted on SME employees in Bali with a total of 165 respondents with 90,91% response rate and total 150 questionnaire returned. Respondents were selected by purposive sampling method, where each research instrument uses a 5 Likert scale measurement. The initial evaluation is carried out by estimating the evaluation of the measurement model that is validity and reliability of each reflective construct. The evaluation of structural models for testing research models using the WarpPLS 4.0 program. The significance of the parameters is determined by resampling bootstrapping and using 500 sub-samples of equal size to that of the original sample. The results of this study provide a view that entrepreneurial commitment as an antecedent capable to influence entrepreneurial orientation of SME employees in Bali, be proven of each entrepreneurial commitment dimensions. Entrepreneurial orientation can be predicted by affective commitment of SME employees in Bali significantly. Calculative commitment can influence entrepreneurial orientation of SME employees in Bali not significantly. Entrepreneurial orientation predicted by normative commitment of SME employees in Bali significantly. Keywords: commitment, affective, calculative, normative, entrepreneurial orientation JEL Classifications: L1, L26 DOI: https://doi.org/10.32479/irmm.8971